Simulated development and optimized performance of narrow-bandgap CsSnI3-based all-inorganic perovskite solar cells. (27th August 2021) - Jiang, Mengying; Tang, Jiyu
Abstract: As perovskite solar cell (PSC) technology is about to be commercialized, the use of toxic and organic material is still a problem. At the same time, CsSnI3 has received widespread attention because of its narrow bandgap and non-toxicity. In this study, we use the wxAMPS tool to investigate the limitations of Sn-based all-inorganic PSCs, using CsSnI3 perovskite as the absorption layer and Au as the back electrode to create non-toxic all-inorganic PSCs. CsSnI3 is a narrow-band material; the absorption range can be extended to the near-infrared spectral region, and it has a very high hole mobility. Therefore, this article first compares several potential inorganic electron and hole transport layers (ETLs and HTLs), and the results show that C60 ETL and MoOx HTL are the most suitable materials. Moreover, the device performance is further improved by optimizing the absorber thickness as well as the doping density. Under optimized conditions, a conversion efficiency of 19.25% is obtained for the FTO/C60 /CsSnI3 /MoOx/Au PSCs, indicating that there is much room for further performance enhancement. The photovoltaic performance parameters achieve their optimum value at an absorber thickness is better among the range of 100–1300 nm and doping density of 10 19 cm −3 . This shows that the proposed non-toxic all-inorganic PSCs have broad prospects in future photovoltaic and optoelectronics applications, and provide theoretical guidance for the manufacture of a non-toxic and inorganic PSCs.